PENGARUH MODEL TALKING STICK BERBANTUAN LEAFLET TERHADAP HASIL BELAJAR SISWA MATERI SISTEM GERAK MANUSIA KELAS VIII SMP - Marlena, Maria; Ningsih, Kurnia; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of cooperative learning talking stick assisted leaflet models on student learning result motion systemin human materials in class VIII SMP Negeri 11 Pontianak. Form of research of quasy experimental with nonequivalent control group design. The sampling technique used was intact group, with class VIII A as experiment class and class VIII B as control class. The instrument is a multiple choice test of 20 items. The results showed the score an average learning result of the experimental class is 16.48 while the control class is 14.67. Based on U-Mann-Whitney test result, it is obtained Z count (-6,78) <-Z table (-1,96), it can be concluded  that there difference between student learning result which is taught using cooperative talking leaflet-assisted talking stick model and conventional model. The effect size value obtained was 1,27 with a category of moderate and gave the effect of  39,80%. Keywords : Talking stick, Leaflet, learning result, motion system in humans